FENOMENA URBANISASI DAN KEBIJAKAN PENYEDIAAN PERUMAHAN DAN PERMUKIMAN DI PERKOTAAN INDONESIA - Mita Noverina (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2010)
Indonesia has been experiencing urbanization since the last decades. The level and the pace of urbanisation differ among provinces and cities, those which are located in Java are more urbanised compared to those in the outer islands. Various factors contribute to the fast growth of urban population. Similar with other less developed countries in general, the high rate of population migration from rural to urban areas are the most dominant factors inducing rapid urban population growth. Since economic activities and development programs in general are more concentrated in urban areas, migration of rural dwellers to urban areas is inevitable. Rural inhabitants move to the cities in order to gain access to economic activites. However, urbanisation creates problems for urban governments, especially those responsible in meeting the needs of the populace. Growing needs of housing and its supporting facilities and infrastructures are a crucial problem for the rapidly growing urban population. In fact urban governments, in collaboration with other parties, have carried out various efforts to provide housing, including for the poor and the migrants who mainly gain low and uncertain income. However the last group seems to be excluded from the benefits. Due to the limited amount of money they have, the majority of the poor and the rural to urban migrants cannot afford for reciding houses provided by the government. This forces them to reside in slums and squatter settlements that lack of various housing facilities and infrastructures. Therefore, urban governments have to conduct other attempts to provide affordable shelters for the poor.Keywords: urbanisasi; migrasi desa kota; perumahan dan permukiman